Thyroid diseases before pregnancy in the pregnant state and postpartum - Tkaczuk-Włach, Joanna; Sobstyl, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2012)
The most common thyroid disorders in pregnancy are hypothyroidism and subclinical hypothyroidism. Clinical hyperthyroidism during pregnancy is much less common. Thyroid disorders are associated with many pregnancy complications. Thyreotoxicosis is usually caused by Graves-Basedov disease and is associated with miscarriage, placental abruption, fetal hyperthyroidism, preeclampsia and preterm birth. The most common cause of hypothyroidism in women of reproductive age and in pregnancy is autoimmune thyroiditis. Hypothyroidism in pregnancy has been recognized as a cause for increased rates of miscarriages, placental abruption, many neonatal complications and lower intelligence scores in progeny. Subclinical and overt hypothyroidism require during pregnancy treatment with levothyroxine.